MON-717 Novel GLI2 Mutations Identified in Pediatric Patients with Combined Pituitary Hormone Deficiency: One Gene, Various Genotypes - Vishnopolska, Sebastian A (J Endocr Soc, 2020)
Combined pituitary hormone deficiency (CPHD) is an important clinical problem caused by mutations in more than 30 different genes. Six genes in the Sonic Hedgehog (SHH) signalling pathway are reported to cause CPHD. SHH signaling is essential to induce pituitary cell identity in cells of Rathke’s pouch by stimulating expression of the transcription factors Lhx3 and Lhx4. In the absence of SHH signaling, a repressive isoform of the transcription factor GLI2 (Gli-Kruppel family member 2) suppresses gene expression. In the presence of SHH signaling, the activating form of GLI2 gains access to the nucleus and induces expression of downstream target genes. Heterozygous GLI2 loss of function mutations are found in patients with holoprosencephaly (HPE), HPE-like phenotypes associated with pituitary anomalies, and combined pituitary hormone deficiency with or without other extra-pituitary findings. We sought to identify the cause of CPHD in 171 unrelated patients diagnosed with or without extra-pituitary manifestations that were recruited from several Argentinean medical centers. We conducted panel sequencing, and identified GLI2 heterozygous variants that were rare and predicted to be deleterious in two unrelated patients, (p.L761P and p.1404Lfs) and a single, heterozygous, rare, likely deleterious GLI2 variant identified by exome sequencing (p.A203T). p.L761P and p.A203T variants were previously reported as candidates for HPE/CPHD, no functional studies were carried out to determine the effect of the variants on the gene function. We performed functional analysis of these variants using a mammalian cell line (NIH/3T3-CG) previously engineered to be a sensor for SHH signaling. It was stably transfected with a reporter gene that expresses GFP in response to GLI2 activation by a SHH agonist. We modified this cell line to assay GLI2 variants. We created a homozygous knock out of both endogenous Gli2 genes using CRISPR-Cas9 editing, and individual cell clones were selected for loss of GFP expression in response to SHH agonist treatment by FACS. We verified that transfecting the knockout cells with wild type Gli2 restored SHH responsive GFP expression. We assayed the ability of three patient GLI2 variants to rescue GFP expression and SHH agonist responsiveness and found that all three failed to fully rescue to wild type levels. This supports the hypothesis that the GLI2 variants in three CPHD patients are likely pathogenic. Thus, we identified three likely pathogenic GLI2 mutations in CPHD patients from Argentina. The variable phenotype of patients with GLI2 mutations worldwide could be caused by variation in other genes, environmental exposures, maternal effects, and/or epigenetic factors.